Anahada sabada-dasama duāra : anahada sabada dasama duāra de wishe sambandhī khullhā niraṇā - Raṇadhīra Siṅgha, b. 1879 (SAMP early 20th-century Indian books project, 1952)
Sikh method for self-realization.